Blood and Paint: Review of Stephen F. Eisenman, The Cry of Nature: Art and the Making of Animal Rights - Freund, Amy (Humanimalia, 2016)
Stephen F. Eisenman, The Cry of Nature: Art and the Making of Animal Rights. London: Reaktion Books, 2013. 309 pp, 98 illustrations. $29 pbk.